Efeito do bálsamo de copaíba (Copaitéra reticulata ducke) sobre a Germinação de esporos de Fusarium - Diniz, S. P S S; Bonzanini, F.; Bueno, M. A S [UNESP]; Rodrigues, J. D. [UNESP] (My University, 2002)
The germinative capacity of spores of Fusarium was studied in the presence of copahiba balsam (5 to 100%). The culture was carried out in Erlenmeyer flasks with 50ml of ICI medium and 1 ml of the pre-inoculated fungus. In some specific cases, 1 ml of copahiba balsam was added to the medium. The development of spores was significantly reduced in the presence of copahiba balsam. Sensibility to copahiba balsam varied with the different strains of Fusarium.
Effect of copaiba balsam (Copaifera reticulata ducke) on Germination of Fusarium spores
Keywords: Germination; Medicinal plants; Pest biological control; copaifera reticulata extract; plant extract; unclassified drug; antifungal activity; apparatus; controlled study; copaifera reticulata; culture medium; drug effect; fungal spore germination; fungal strain; fungus culture; fungus spore; Fusarium; inoculation; medicinal plant; nonhuman; strain difference; Copaifera; Copaifera officinalis; Copaifera reticulata; Fungi